Union of the Comoros : Second Review Under the Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2006)
This paper on the Second Review Under the Staff-Monitored Program for the Union of the Comoros reports that the external current account is expected to worsen with the sharp deterioration of the trade deficit. General economic conditions have remained lackluster in 2005, hampered by the sharp deterioration in terms of trade, as vanilla prices have remained depressed and oil import costs have more than doubled. Monetary policy has remained prudent and inflation subdued.